“SEX TRAFFICKING” IN CYBERSPACE AND THE POTENTIAL FOR LEGAL INJUSTICE: A CYBERFEMINISM STUDY - Kusnaini, Kusnaini (Jurnal Hukum Khaira Ummah, 2024)
The advancement of information and communication technology has provided many changes and conveniences to all levels of society. One of them is the development of internet technology that can be accessed by everyone. The existence of the internet network has provided many benefits to its users, such as a means of education or learning, a means of technology-based economic development, a means of online business transactions, a means of sharing news and stories, as a means of social interaction, and so on. The development of internet technology that affects various aspects of life, causes humans to live in two different worlds, namely the world (space) in the real sense and the cyber world (space). All human needs and survival can now be accessed only through the internet network so that it has created a world relationship that is limitless or borderless. Borderless is a term that with the advancement of technology, the latest information can be accessed anytime and anywhere, and the world community can reach each other without being hindered by language, distance, and time differences.